EVALUASI APLIKASI SISTEM INFORMASI MANAJEMEN DAN AKUNTANSI BARANG MILIK NEGARA (SIMAK BMN) DALAM KAITANNYA DENGAN NILAI ASET TETAP PEMERINTAH PADA DIREKTORAT JENDERAL BIMBINGAN MASYARAKAT HINDU KEMENTERIAN AGAMA RI - Ni Luh Putu Sri Juliyanti; Susi Dwimulyani (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2015)
The purpose of this study is to find out the implementation procedures of SIMAK BMN application, and also to evaluate its procedure and its output in order to create accountability and transparency. This research was conducted in the office of Ministry of Religious Affairs at center working unit Directorate General of Guidance for Hindu Community. The part of SIMAK BMN application procedures implementations that have been studied were in the recording of the government fixed assets. The output of SIMAK BMN application is presented in the Financial Balance Sheet Report of Directorate General of Guidance for Hindu Community. The results of this study indicate that the implementation of SIMAK BMN application has been appropriate with the applicable regulations, and it has created accountability. However, the output of SIMAK BMN application has not created transparency yet because at the moment the public are still unable to access this information yet.